TILRR Promotes Migration of Immune Cells Through Induction of Soluble Inflammatory Mediators - Kashem, Mohammad Abul; Ren, Xiaoou; Li, Hongzhao; Liang, Binhua; Li, Lin; Lin, Francis; Plummer, Francis A.; Luo, Ma (Frontiers in Cell and Developmental Biology, 2020)
TILRR has been identified as an important modulator of inflammatory responses. It is associated with NF-κB activation, and inflammation. Our previous study showed that TILRR significantly increased the expression of many innate immune responsive genes and increased the production of several pro-inflammatory cytokines/chemokines by cervical epithelial cells. In this study, we evaluated the effect of TILRR-induced pro-inflammatory cytokines/chemokines on the migration of immune cells. The effect of culture supernatants of TILRR-overexpressed cervical epithelial cells on the migration of THP-1 monocytes and MOLT-4 T-lymphocytes was evaluated using Transwell assay and a novel microfluidic device. We showed that the culture supernatants of TILRR-overexpressed HeLa cells attracted significantly more THP-1 cells (11-40%, p= 0.0004 to 0.0373) and MOLT-4 cells (14-17%, p= 0.0010 to 0.0225) than that of controls. The microfluidic device-recorded image analysis showed that significantly higher amount with longer mean cell migration distance of THP-1 (p< 0.0001 to 0.0180) and MOLT-4 (p< 0.0001 to 0.0025) cells was observed towards the supernatant of TILRR-overexpressed cervical epithelial cells compared to that of the controls. Thus, the cytokines/chemokines secreted by the TILRR-overexpressed cervical epithelial cells attracted immune cells, such as monocytes and T cells, and may potentially influence immune cell infiltration in tissues.